Understanding the Effect of Entrepreneurship Education on Students' Entrepreneurial Intentions - Ilham Abu; Sutrisno Sutrisno (Universitas Negeri Makassar, 2024)
This research investigates the impact of entrepreneurship education on the entrepreneurial intentions of vocational school students. The study employs a quantitative research methodology, utilizing observation, questionnaires, and documentation as data collection methods. The target group comprises students who have received entrepreneurship education, and the study uses their responses as the research sample. Data were gathered through questionnaires based on a Likert scale, with reliability and validity tests conducted to ensure accuracy. Simple linear regression analysis was then applied to interpret the data. The findings reveal that entrepreneurial knowledge significantly influences students' intentions to engage in entrepreneurship. The relationship between entrepreneurial knowledge and entrepreneurial interest is strong and positive, indicating that as students' understanding of entrepreneurship increases, so does their intention to pursue entrepreneurial activities. Conversely, a lower level of entrepreneurial knowledge is associated with a diminished interest in entrepreneurship. These results underscore the importance of entrepreneurship education in shaping students' entrepreneurial ambitions, suggesting that enhanced knowledge can effectively foster a greater desire among students to embark on entrepreneurial ventures.